Highly efficient and selectivity removal of heavy metal ions using single-layer NaxKyMnO2 nanosheet: A combination of experimental and theoretical study. (July 2021) - Peng, Ruichao; Li, Hao; Chen, Yongting; Ren, Feipeng; Tian, Fengyu; Gu, Yawei; Zhang, Honglei; Huang, Xiurong
Abstract: Manganese oxides (MnO2 ) are widely applied in heavy metal ions removal due to their low-cost, environmental-friendly and biocompatibility. However, the adsorption capacity of MnO2 need to be further improved to satisfy the demand of practical application. Herein, a highly dispersed single layer Na x K y MnO2 nanosheet was synthesized by a facile wet-chemical method with sodium dodecyl sulfonate as surfactant. The high surface specific area, excellent dispersibility and abundant oxygen vacancies endowed Na x K y MnO2 nanosheets with potential in heavy metal ions adsorption. The adsorption experiments results showed that Na x K y MnO2 nanosheets possessed high efficiency and selectivity towards lead ion (Pb 2+ ) with a high adsorption capacity of 2091.8 μmol g −1 . The Na x K y MnO2 also showed an excellent reusability with the removal rate of 95.4% for Pb 2+ even after five cycles. Moreover, both the theoretical calculation and experimental data illustrated that the single layer Na x K y MnO2 nanosheets possess high selectivity to Pb 2+ adsorption. Graphical abstract: Image 1 Highlights: A highly dispersed single layer Na x K y MnO2 nanosheet was synthesized. Physical and chemical properties endowed Na x K y MnO2 with potential in HMI adsorption. Na x K y MnO2 possess high selectivity towards Pb 2+ compared to Mg 2+ and Ca 2+ . Na x K y MnO2 exhibited a record-high Pb 2+ adsorption capacity of 2091.8 μmol g −1 . Na x K y MnO2 showed excellent reusability with Pb 2+ removal rate of 95.4% (5 cycles).